Comparison of two devices to simulate vision with intraocular lenses - Wahl, Siegfried (Clin Ophthalmol, 2019)
INTRODUCTION: The simulation of vision with intraocular lenses (IOLs) prior to the clinical validation is of great interest for manufacturers as well as clinicians. We have tested the influence of different IOLs on the perception of contrast using different devices. MATERIALS AND METHODS: A Rassow telescope and the VirtIOL have been used to assess the contrast sensitivity function (CSF) through monfocal IOL (CT Asphina 409 MP, IOL 1), multifocal IOL (AT LISA tri 839 MP, IOL 2) and extended-depth-of-focus-IOL (TECNIS Symfony ZXR00, IOL3) in 21 participants, aged between 22 and 29 years. Contrast sensitivity (CS) was tested at various spatial frequencies (3–30 cycles per degree), using the Tuebingen contrast sensitivity test. RESULTS: All tested IOL reduced the CS when compared to measurements with a trial lens correction of refractive errors. The analysis of the area under the curve of the contrast sensitivity function (AUC-CSF) revealed a significant reduction compared to the trial lens correction in case the Rassow telescope was used (IOL 1: P=0.008; IOL2: P<0.001; IOL3: P<0.001) and the same was true for the VirtIOL device for IOL2 and IOL3 (IOL2: P<0.001; IOL3: P<0.001), but not for IOL1 (P=0.192). Interdevice analysis of the AUC-CSF revealed significant differences for IOL1 and IOL2 (IOL1: P=0.025; IOL2: P<0.001), while no difference was found for IOL3 (P=0.092). Bland–Altman analysis as well as intraclass correlations coefficients indicated only weak interdevice agreement for the tested IOL. CONCLUSION: The assessment of the interdevice analysis for the Rassow telescope and the VirtIOL device revealed only a minor agreement between the two devices. In order to investigate vision with IOLs prior to a clinical validation, the use of the VirtIOL device is recommended.